O drama por trás de uma promessa: uma vida anulada na casa ‘DUSZÔTRO’ - SOUSA, Bruno José Ferreira de (2024)
This undergraduate thesis aims to develop a dramaturgy based on the life story of Rosa Maria Ferreira de Sousa, my mother, a riverside woman who, at the age of 12 in 1966, left her relatively tranquil life in the interior of Marajó (PA) and migrated to Belém do Pará, under the promise of studying and having a better life. However, upon arriving in the city, she was confronted with a harsh reality: domestic exploitation under conditions akin to slavery. The research process involves my own memories and an interview with my mother. The dramaturgy to be constructed aims to highlight a sad yet common story in our region and expose the reality of domestic exploitation, especially of pre-adolescent girls. The work does not seek to portray literally all the challenges faced by my mother, but rather to create powerful scenes inspired by personal experiences and the injustices she witnessed with other domestic workers who dared to question the conditions to which they were subjected, as well as scenes I witnessed as the son of Ms. Rosa, who was sponsored by one of her employers. Through this dramaturgy, titled "Duszôtro," the goal is to invite the audience to reflect on the existence of domestic exploitation and its relevance in the current social context. The work aims to provoke reflection on social inequality, human rights violations, and the importance of combating this form of exploitation. It also encourages actions and public policies focused on protecting victims and promoting gender equality.